EFFECTIVE STRATEGIES FOR TEACHING THE ALPHABET TO YOUNG LEARNERS: A COMPREHENSIVE APPROACH - Safiya Solihova Azamatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract:Generally, alphabet is the foundation of any language. Learning the alphabet is one of the first and important steps in early childhood education. This article will explore and provide effective methods for teaching the alphabet to children by analyzing best practices and strategies in pedagogy, cognitive development, and educational psychology. Teachers are responsible for giving right approach in teaching the alphabet since it is the fundamental part of children’s speech.